Estimating typical sediment concentration probability density functions for European rivers - Becvar, Martin (Cranfield University, 2005)
Sediment in rivers is linked with qualitative and quantitative water problems throughout Europe. Sediment supply and transfer are part of a natural process of minimising gradients in the landscape. However, since human activities have started to affect the equilibrium, sediment supply is often out of balance with the river system. Cases of either low or high concentration often mean an instability which may cause severe problems. Therefore it is highly important to gain knowledge about sediment patterns in catchments as a part of catchment management. This study was undertaken in order to improve sediment modelling in the GREAT-ER point source pollution river modelling package which currently uses suspended sediment concentration of 15 mg.l-1 for all rivers in Europe, which is an obvious oversimplification. There are three aims for this thesis; one to investigate the range of suspended sediment yields from major European catchments (44 catchments investigated), two the verification of sediment delivery equations and three to develop a methodology to predict suspended sediment concentration from sediment yield in these rivers. Coarse sediment and bed load are not investigated in this study. Monitored river sediment concentration data were analysed and compared to sediment yields obtained using the well established sediment delivery ratio (SDR) approach. Several SDR equations were tested. Equations where the area of the catchment was used as the sole variable provide the best results. In addition, sediment yields were estimated based on the recent PESERA soil erosion map for Europe. Annual sediment yields were finally predicted using three relationships between observed yields and catchment characteristics. A method to predict sediment concentration at different flow exceedance rates was successfully developed and provides satisfactory results. The basic principle of the method is redistribution of annual sediment yield into annual water volume using flow characteristics at the point of interest. Further investigations with an emphasis on sediment data and refining the methodology were suggested in order to improve concentration modelling.